2013
DOI: 10.3382/ps.2012-02933
|View full text |Cite
|
Sign up to set email alerts
|

Cool perches improve the growth performance and welfare status of broiler chickens reared at different stocking densities and high temperatures

Abstract: The present study investigated the interaction of stocking density and cool perch availability on broiler chickens raised at high ambient temperature (>30.8°C). Behavior, live performance, and the incidence of footpad and hock burns and abdominal plumage damage were investigated over a 4-wk experimental period. A total of 1,152 one-day-old Arbor Acres chicks were subjected to a 2 (cool perches) × 3 (stocking densities) factorial arrangement of treatments. From 1 d of age, birds were provided with or without co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
14
2
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 36 publications
7
14
2
1
Order By: Relevance
“…Martrenchar et al () reported higher final body weights (2%) due to the presence of perches at a density of 22 birds/m 2 , males being slightly heavier, but not at other stocking densities. Similar results were reported by Zhao et al () after 6 weeks, and also by Zhao et al () but only at densities of 20 birds/m 2 . Perching frequency was significantly higher when birds were raised at stocking densities of 15 or 20 birds/m 2 (Pettit‐Riley & Estevez ).…”
Section: Resultssupporting
confidence: 91%
“…Martrenchar et al () reported higher final body weights (2%) due to the presence of perches at a density of 22 birds/m 2 , males being slightly heavier, but not at other stocking densities. Similar results were reported by Zhao et al () after 6 weeks, and also by Zhao et al () but only at densities of 20 birds/m 2 . Perching frequency was significantly higher when birds were raised at stocking densities of 15 or 20 birds/m 2 (Pettit‐Riley & Estevez ).…”
Section: Resultssupporting
confidence: 91%
“…Similar results were reported by Pettit-Riley and Estevez (2001), Estevez et al (2002), and Ventura et al (2012). Although Zhao et al (2013) reported beneficial effects of cooled perching on feed conversion ratio and body weight gain, these effects were related to a thermoregulatory advantage of the cooled perches. Availability of perching might not affect these criteria, probably due to relatively low use of the perches by fast-growing broilers.…”
Section: Discussionsupporting
confidence: 76%
“…breast, thigh, wing, and back) were not affected by perch availability in this study. Zhao et al (2013) reported similar results with regard to carcass yield and proportions of carcass parts. Low perch use in the perch group, along with similar growth performance, may explain similar proportion of carcass parts in both groups in the current study.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Generally, the common indicator of a good perch (material and configuration) is preference of perch use. However, data collection of perching preference in most experiments has been performed by manual observations (Brendler and Schrader, 2016;Campbell et al, 2016;Nasr et al, 2012a;Norring et al, 2016;Steenfeldt and Nielsen, 2015;Zhao et al, 2013), which is time and labor intensive and limited in duration of observation. Hence, several automatic methods have been developed to monitor perching behavior including using load cells, computer vision and radio frequency identification (RFID) technology.…”
Section: Introductionmentioning
confidence: 99%